Polish Constitutional Tribunal Judgments with “Deferral Clause” and Their Application by Polish Courts - Ciżyńska-Pałosz, Angelika (Teisė, 2020)
The main aim of this paper is to present the specificity of functioning of the Polish Constitutional Tribunal, the characteristics of one type of its judgments, i.e. verdicts with a “deferral clause” and preparation of the de lege lata and de lege ferenda postulates. Problems analyzed in this work remain valid in both jurisprudence and legal doctrine.
Keywords: Polish Constitutional Tribunal; judgments of the Constitutional Tribunal; execution of judgments of the Constitutional Tribunal; constitutional law; judiciary